Experimental Study on Fire Resistance of Geopolymer High-Performance Concrete Prefabricated Stairs - Yongjiang Shen; Qilin Wang; Quan Zhou; Xinxing Li; Zhengliang Xiang (Buildings)
Geopolymer-based high-performance concrete (GHPC) stairs have been proposed as an alternative solution that fulfills both lightweight and load-bearing requirements for prefabricated stairs. Nevertheless, the fire resistance properties of GHPC stairs remain uncertain. Therefore, this study first conducts high-temperature experimental research on GHPC test blocks. The experimental results demonstrated that the GHPC test blocks exhibited no signs of bursting at elevated temperatures and displayed less degradation in the compressive strength compared to that of ordinary concrete. Subsequently, GHPC-Z stair specimens with ribbed and unribbed configurations were fabricated to conduct a fire resistance test at elevated temperatures, followed by a comparative analysis of the resulting damage. The test results indicate that both types of GHPC stairs demonstrate exceptional performance without exhibiting bursting or noticeable cracks or structural spalling marks on their main bodies, despite experiencing vertical deformation. Furthermore, based on these findings, finite element models were established to simulate the fire-induced damage in GHPC and ordinary concrete stairs without ribbed folding plates. The simulation results illustrate that GHPC stairs possess commendable fire resistance capabilities along with an ability to effectively recover from high-temperature damage.